Probe into ATO Train System Application to Train Control System of Intercity Passenger Dedicated Line - WU Jin-shui; TANG Guo-ping (机车电传动)
In the light of the operation demand of the intercity passenger dedicated line, scheme was proposed to increase an ATO function based on the existing CTCS-2 level train control system. The composition of the combination program of CTCS-2 level and ATO train control system was briefed along with the working principle of ATO, and main analysis was carried out for the function realization of ATO system in intercity passenger dedicated line. The execution of the program, which was good for implementing intelligentizing and automatism of transport dispatch command and control, would maintain transport safety, improve transport efficiency, and optimize transport organization.